19.7k views
2 votes
Two functions are shown below

f(x)=8x+10
g(x)=6x-4

What is f(4)-g(3)?

Two functions are shown below f(x)=8x+10 g(x)=6x-4 What is f(4)-g(3)?-example-1

2 Answers

10 votes
C answer final because f(x) = f(4); g(x) = g(3)
f(4)= 8(4)+10= 42
g(3)= 6(3)-4= 14
f(4)- g(3)= 42-14= 28
User Schnodderbalken
by
5.2k points
13 votes

Answer:

c.28

Explanation:

Given

f(x) = 8x + 10 and g(x) = 6x - 4

f(4) = 8*4 + 10

= 32 + 10

= 42

g(3) = 6 * 3 - 4

= 18 - 4

= 14

Now

f(4) - g(3)

= 42 - 14

=28

hope it will help :)

User Monalisa Das
by
5.2k points